A Comparative Account of Statutory Interpretation in Singapore - GOH, Yihan (Institutional Knowledge at Singapore Management University, 2008)
In 1993, the Singapore Parliament enacted legislative provisions adapted from Australian legislation directing, inter alia, that the courts apply the purposive approach in statutory interpretation. Those provisions also allowed for the extended use of extrinsic materials in the interpretative process. Fifteen years on, there is now a considerable body of Singapore case law to which a meaningful analysis may be undertaken. Indeed, from an initially cautious application of the enacted legislation, the courts began to read the enactments expansively, eventually providing for a statutory interpretation regime that is largely free of the confines of old. Nonetheless, the Singapore position does lend itself to some unique problems, as there are signs that the courts have in a limited number of cases evinced an intention to reverse the hitherto rather expansive approach. This article provides a brief overview of the evolution of the Singapore position to its present form, before making a brief comparison with parallel developments in Australia, from which Singapore's provisions originated. It will then attempt to explain the present Singapore position in relation to statutory interpretation as distinguished from that taken in Australia. It is hoped that the account provided in this article will be of comparative interest to jurisdictions which have adopted similar legislative reform and, more broadly, to the enduring problem of the proper approach towards statutory interpretation.